Synchronous parallel kinetic Monte Carlo simulation of AL3SC precipitation - Moura, Alfredo (2015)
The main objective of the present work is to profound the applicability of a synchronous parallel kinetic Monte Carlo (spkMC) algorithm for simulating the nucleation of Al3Sc precipitates. Parallel processes communication is implemented through Message Passing Interface (MPI). Consequently, the capability of extending time and length scales of atomistic kinetic Monte Carlo (kMC) will be attested. Lastly, we present the results obtained from simulations of nucleation of Al3Sc precipitates, which include a comparative view between sequential and parallel algorithms.